Interest rates and fiscal consolidation programs - Estorninho, Pedro Afonso Mateus (2022)
We claim that changes in the interest rate impose impacts on multipliers of fiscal consolidations programs. We use the database and extend the regression in Alesina et al. (2015a)with interest rates to check the relationship with fiscal multipliers. Then, we adapt the overlapping generations model with incomplete markets used in Brinca et al. (2021) and fix the wage and interest rate. Using that adaptation of the model, we assess the impact of a change in the interest rates of three calibrated European economies. We then test the mechanism and compare the impacts based on countries’ different Gini coefficients and percentage of agents constrained. For both analysis we conclude that there is a negative relationship between the interest rate and fiscal consolidation multipliers under a fixed wage and interest rate environment. We also conclude that countries with higher percentage of agents constrained are more resistant to changes on interest rates.